PARTIAL DISCHARGE DIAGNOSTICS IN ELECTRIC MOTORS EXPOSED TO AMBIENT STRESSES DURING INDUSTRIAL OPERATIONS - Hassan W.; Hussain G.A.; Firuzi K.; Ariffin A.M.; Kay J.A. (Institute of Electrical and Electronics Engineers Inc., 2025)
In this paper the effect of contamination under varying temperature and relative humidity (RH) in electrical electric motors? (EM) insulation is investigated through partial discharge (PD) diagnostics. The variations in PD intensity have been investigated under varying environmental conditions. For this purpose, PD measurements were carried out within an artificial industrial environment inside a climate-controlled chamber. Various PD features were extracted to study probability distribution functions to further investigate the PD severity at various levels of contamination, under varying temperatures and RH. Based on the experimental outcomes, it was revealed that PD activity within the EM insulation was significantly affected by temperature and RH under varying contamination conditions. The proposed methodology is believed to be helpful in achieving the desired level of reliability for a wide range of industrial applications exposed to ambient stresses. ?2024 IEEE.